Effect of Benzyl adenine ( BA) on In vitro Initiation of Pear Pyrus communis L and Apple Malus domestica Borkh Rootstocks - Mohammed Ahmed Kareem; Zainab Abduljabar Hussain; Tagreed Abduljabar; Nora Sahib; hyfa muhssen Bander (Journal of Madenat Alelem University College, 2014)
The effect of different concentrations of Benzyl adenine (BA) (0, 0.25, 0.5, 1.0 mg/l) was studiedon two types of media (MS1, MS2), which determined with 0.25 mg/L IBA and 0.25 mg/L IAA, respectively. These were culturedon initiation and growth stageafter existed from trees of Pear Pyruscommuis L. and Apple Malus domestica Borkh( MM106) rootstocks which incubated at 25± 2 ˚C and 16 hr photo period with light intensity of 1000 Lux. Data of shoots number, length, leaf number were taken after 8 weeks. Results showed that adding of BA on two types of media caused significant effect in all characters, which BA at 1.0 mg/L superior to give highest rate of shoot number reached 1.8 shoot/ plant while, BA at 0.5 mg/L gave highest rate in shoot length and number of branch reached 2.44 cm/plant and 8.0 shoot/plant, respectively. The rootstock PyruscommuinsL. was proved to be the best than Malus domestica Borkh(MM106) rootstock in all characters at two types of medium.